Study on the influence of localised thermal load on collapse strength of stiffened panels under longitudinal compression. (15th July 2021) - Cai Xu, Ming; Jun Song, Zhao; Jin Pan,; Wang, Tao
Highlights: The thermal load could produce biaxial stress state and then reduce the load carrying capacity of stiffened panels. The geometrical range of model is suggested extent half span/bay for reducing the influences of boundary conditions. The ultimate strength of the stiffened panels would achieve during thermal load. The residual thermal stress should be taken into account in the assessment of residual ultimate strength. Abstract: The purpose of the present study is to investigate the influences of localised thermal stress on the load carrying capacity of stiffened panels under in-plane compression. The thermal loads and bending moment caused by extreme water wave seldom occur at the same time, hence, which are applied on ship structures in two load steps separately in the finite element (FE) analysis. Firstly, the stress state and structural responses of the stiffened panels under localised thermal loads with different heating zone ranges are discussed. Subsequently, the collapse behaviours of the stiffened panels under in-plane compression are simulated, in which the residual thermal stress due to the thermal loads is also included. The influences of residual thermal stress, areas of heating zone and boundary conditions on the collapse behaviours are investigated. It is found that the thermal loads could cause biaxial stress state that can reduce the load carrying capacity of the stiffened panels, which should be considered in the development of assessment formula of residual ultimate strength for ship structure design.